Aerodynamic behavior of a discus - Seo, K.; Shimoyama, K.; Ohta, K.; Ohgi, Y. (Procedia Engineering, 2012)
To determine the flight path of a discus when it is thrown, it is essential to know what aerodynamic forces are acting on it. However, little data on this is available. Employing a full-size model in a wind tunnel, we have measured the aerodynamic forces acting on a discus spinning on its transverse axis, as well as on a `non-spinning` discus. The aerodynamic force data (drag, lift and pitching moment) were obtained to create an `aerodynamic database`. These forces are given as functions over practical ranges of the angle of attack, the spin rate and the wind speed. It was found that the stalling angle was about 30°, and that the lift coefficient increased linearly with increasing angle of attack up to the stalling angle. The estimated lift coefficient obtained by the vortex lattice method agrees with the experimental data within a standard deviation of 0.08. It was observed by oil flow and smoke observation methods that a pair of longitudinal vortexes occur from the `pressure side` to the `suction side`, similar to wing-tip vortices. These longitudinal vortexes prevent flow-separation up to a high angle of attack, around 30°. The drag coefficient increases with increasing angle of attack up to the stalling angle, and it decreases slightly around the stalling angle, corresponding to a significant and abrupt decrease in lift at the same angle. The coefficient of the pitching moment is almost positive, which is the case with `nose-up` rotation. There is little difference between the aerodynamic coefficients whether the discus is spinning or not.